2013
DOI: 10.2298/tsci111219051t
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study on waste heat recovery from internal combustion engines using organic Rankine cycle

Abstract: There are a substantial amount of waste heat through exhaust gas and coolant of an Internal Combustion Engine. Organic Rankine cycle is one of the opportunities in Internal Combustion Engines waste heat recovery. In this study, two different configurations of Organic Rankine cycle with the capability of simultaneous waste heat recovery from exhaust gas and coolant of a 12L diesel engine were introduced: Preheat configuration and Two-stage. First, a parametric optimization process was performed for both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Generally waste heat recovery is a technique, which enhance the performance of engine and can reduce the brake specific fuel consumption (bsfc) and consequently thermal efficiency is improved. Tahani et al [3] showed the waste heat recovery from 12 lt. CI engine using organic Rankine cycle. In the study, two different configuration of organic Rankine cycle (ORC) for waste heat recovery from exhaust gas and coolant: preheat configuration and two stage configuration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Generally waste heat recovery is a technique, which enhance the performance of engine and can reduce the brake specific fuel consumption (bsfc) and consequently thermal efficiency is improved. Tahani et al [3] showed the waste heat recovery from 12 lt. CI engine using organic Rankine cycle. In the study, two different configuration of organic Rankine cycle (ORC) for waste heat recovery from exhaust gas and coolant: preheat configuration and two stage configuration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ryms et al [50] adapted the pinch analysis to realize the parameter fitting so as to improve the ORC design process. Based on the research work of many researchers, the optimistic forecast of ORC efficiency is generally between 15-20%, whereas the realistic expectation lies generally between 7-10%, which at present cannot be larger than 14% [54][55][56][57]. According to the work of Cummins Inc., a 5.4% increase in thermal efficiency can be gained by utilizing the ORC of waste heat of exhaust gas in its Series 8 truck engines [52].…”
Section: Thermodynamic Cycle Of Organic Rankine Cyclementioning
confidence: 99%
“…In the presented plant, three sources of heat generation including heat recovered from diesel engine, auxiliary boiler, and heat absorbed by evacuated tube collectors (ETC) are available. The outlet temperatures in the first two equipments are usually in the range of 80-100 C [16,17]. In addition, an ETC can easily achieve during its operation relatively high water temperature levels approaching 100 C [18].…”
Section: Energy Analysismentioning
confidence: 99%